Integração ensino-serviço: implicações e papéis em vivências de cursos de Graduação em Enfermagem - Brehmer, Laura Cavalcanti de Farias; Ramos, Flávia Regina Souza (Revista da Escola de Enfermagem da USP, 2014)
The study aimed at understanding the implications of the teaching-service integration to nursing education from the perspective of teachers, students and professionals in Primary Healthcare as well as identifying the roles of teachers and professionals who follow practical experiences in education. This is a case study of qualitative approach carried out in five undergraduate courses in Nursing in the state of Santa Catarina. A total of 22 teachers and 14 professionals were interviewed and five focus groups were conducted with students. Results are presented in two categories: Implications of the teaching-service integration to education in Nursing: contributing factors and intervening factors and Relationships established in the experiences: a unison speech and a dissonant practice. The contributions of the teaching-service integration are undeniable. Despite this belief, there are intervening factors that need to be on the agenda for discussion. The role of facilitator in education emerged strongly despite conflicting perceptions remain.